DEVELOPMENT OF HYPERTROPHY IN SKI JUMPERS - Kryuchkov, A.S.; Fendel, T.V.; Zubkov, D.A. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to theoretically substantiate the feasibility of developing hypertrophy in ski jumpers. Methods and structure of the study. The main research method was the method of analysis and generalization of scientific and methodological literature data. Results and conclusions. During the study, the following conclusions were made: exercises with a hypertrophic effect are an effective tool for increasing the strength potential of skeletal muscles; hypertrophic "response" of the athlete's skeletal muscles, as a response to power loads, depends on two groups of factors: congenital and acquired; strength exercises used for the purpose of myofibrillar hypertrophy must meet two requirements: to ensure the involvement of the maximum number of muscle fibers in the composition of the working (loaded) muscles and to ensure the maximum tension of each muscle fiber; an increase in myofibrillar hypertrophy requires special training to transform the strength effect into the power of motor efforts; skeletal muscle hypertrophy threatens to reduce the speed of the competitive exercise in ski jumpers.